Effects of Selected Nigerian Medicinal Plants on the Viability, Mobility, and Multidrug-Resistant Mechanisms in Liver, Colon, and Skin Cancer Cell Lines - AlQathama, Aljawharah; Ezuruike, Udoamaka F.; Mazzari, Andre L. D. A.; Yonbawi, Ahmed; Chieli, Elisabetta; Prieto, Jose M. (Frontiers in Pharmacology, 2020)
The aqueous extracts of 26 popular medicinal plants widely used in this country were tested for their in vitro (i) cytotoxicity against a panel of liver (HepG2), colon (Caco2) and skin (B16F10) cancer cells; (ii) antimigratory effects using a 2D model; (iii) effects on cell drug resistance mechanisms including P-glycoprotein (P-gp) efflux activity in Caco2 cells, modulation of intracellular levels of gluthatione in HepG2, ability to scavenge nitric oxide (NO•) and inhibition of tyrosinase-mediated melanogenesis. Daniellia ogea (Leguminosae), Strophanthus hispidus (Apocynaceae) and Annona senegalensis (Annonaceae) were able to exert toxic effects on two different cell lines. Rat melanoma cell proliferation was strongly inhibited by Anogeissus leiocarpus (Combretaceae), Bridelia ferruginea (Phyllanthaceae), and Syzygium guineense (Myrtaceae) extracts all with GI50=50 µg/mL, whilst Alstonia boonei (Apocynaceae), Gongronema latifolium (Asclepiadaceae), and S. hispidus were preferentially toxic against Caco2 (GI50=50, 5 and 35 µg/mL, respectively). Kaya ivorensis (Meliaceae) mildly affected HepG2 cells only (GI50=100 µg/mL). The most active extracts against different drug resistance mechanisms were B. ferruginea (inhibition of P-gp efflux, NO• scavenging and impairing tyrosinase activity) and X. americana (inhibition of P-gp efflux, and GSH depletion). In vitro antimigratory activity against the highly metastatic B16-F10 cell line was shown by A. leiocarpus, Kaya senegalensis (Meliaceae), S. guineense and Terminalia avicennioides (Combretaceae). Some of their bioactive phytochemicals were dereplicated by HPLC and HPTLC.